What do teachers think about youth purpose?. Issue 5 (19th October 2016) - Moran, Seana
Abstract: Life purpose combines personal meaning, future intention, active engagement and expected beyond-the-self impact into a self-regulating beacon for decisions and actions. Interest has grown in how teachers could foster youth purpose. Although studies show relationships between pedagogy and purpose, how teachers themselves understand the concept and view their role in its development need more research. This descriptive, qualitative, secondary analysis of observations and comments of teachers in the United States of America during their normal school days can help teacher educators to instil a purpose orientation in pedagogical training. Teachers are interested in purpose for pupils and for themselves. But they are ambivalent about their efficacy to support purpose development. Currently, purpose is often equated with career rather than with a broader life aim. Personal meaning and engagement are easier purpose dimensions for teachers to design activities for pupils to practice, whereas intention and beyond-the-self impact are less often taught or only addressed abstractly. Specific purpose-related activities are shared to provide ideas for other teachers' own purpose pedagogies.